PENGARUH PENYALURAN KREDIT TERHADAP RETURN ON ASSETS (ROA) PADA BANK BJB KCP LEUWI PANJANG - Karyadi Karyadi; Muthmainnah Masnaya; Sayu Ketut putri (POLITEKNIK PIKSI GANESHA, 2023)
This research has the purpose to analyze the influence of credit distribution to return on asset of Bank BJB. The research methods used are descriptive and verificative with the data collecting techniques through observation, interview and literature review. The data get analyzed by simple linear regression analysis. Based on the research, there is the credit distribution correlation with the return on asset (ROA) in the amount of -0,849 which is in a very strong category. It shows that the significant influence of credit distribution to return on asset (ROA), and the influence given is 72,1% and the rest is 27,9%. It was excluded from the research conducted by the writer. The writer suggests that Bank BJB should offer the installment with varied interest to attract more the debitors in utilizing credit facility given by Bank BJB. Keywords : Credit distribution, Return on asset (ROA), Bank